1994
DOI: 10.1007/bf00731282
|View full text |Cite
|
Sign up to set email alerts
|

Expression of galectins on microvessel endothelial cells and their involvement in tumour cell adhesion

Abstract: Lactoside-binding lectins (galectins) with molecular weights of about 14.5 kDa (galectin-1) and 29-35 kDa (galectin-3) bind preferentially to polylactosaminoglycan-containing glycoconjugates and have been found on the surface of tumour cells and implicated in cell-cell and cell-extracellular matrix adhesion and metastasis. We have demonstrated by immunoblotting that both galectin-1 and galectin-3 are present in extracts of endothelial cells cultured from bovine aorta, rat lung, mouse lung and mouse brain micro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
75
0
4

Year Published

1996
1996
2011
2011

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 122 publications
(85 citation statements)
references
References 42 publications
6
75
0
4
Order By: Relevance
“…Interfering with gal-1 function could (i) prevent metastasis formation through inhibition of gal-1-facilitated tumor cell-EC interactions (22,23), (ii) abrogate tumor escape from immunity through blockade of gal-1-induced apoptosis in activated T lymphocytes (14,20), and (iii) prevent the execution of tumor angiogenesis (this work). This multifunctionality makes gal-1 an excellent target for cancer therapy.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…Interfering with gal-1 function could (i) prevent metastasis formation through inhibition of gal-1-facilitated tumor cell-EC interactions (22,23), (ii) abrogate tumor escape from immunity through blockade of gal-1-induced apoptosis in activated T lymphocytes (14,20), and (iii) prevent the execution of tumor angiogenesis (this work). This multifunctionality makes gal-1 an excellent target for cancer therapy.…”
Section: Discussionmentioning
confidence: 91%
“…Previous studies have shown that gal-1 is key in two mainstays of cancer. First, gal-1 supports metastasis formation, because it facilitates interactions between tumor cells and EC (22,23). Second, it protects the tumor against immunity, because it can induce apoptosis in tumor-infiltrating cytotoxic leukocytes (14,20).…”
Section: Discussionmentioning
confidence: 99%
“…In the case of galectin-9, our data suggest that galectin-9 acts as a L. major-specific tagging protein or an adhesion molecule so that macrophages can recognize L. major more efficiently. It has been known that some galectins, which can cross-link different cells expressing their oligosaccharide ligands (28,34,35), act as adhesion molecules even though galectins are soluble proteins (32,63,64). Galectin-9 contains two CRDs linked by a peptide linker and is thus intrinsically divalent (33,46,65).…”
Section: Discussionmentioning
confidence: 99%
“…Galectin-1 is a beta-galactoside binding protein that is produced by endothelial cells and induces apoptosis in bound activated T cell (Perillo et al 1995;Rabinovich et al 1998;Lotan et al 1994).…”
Section: Deletion Of Activated T Cells By the Livermentioning
confidence: 99%